BUDDHISM IN THE INDIAN SUBCONTINENT: AN ANALYSIS IN THE CONTEXT OF HISTORY AND ARCHAEOLOGY - Daan, Ishwar; Prasad, Pallavi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This article explores the early development of Buddhism in India, with special emphasis on archaeological studies including ancient pillars, stupas and sculptures. Buddhism, founded by Siddhārtha Gautama or the Buddha, emerged in the sixth century BCE and rapidly spread throughout the Indian subcontinent. This article examines the factors behind its success, such as its adaptability to different cultural contexts, the important role of royal patronage – especially the gates of Emperor Ashoka and the establishment of monastic communities. The construction of stupas and other archaeological complexes also played an important role in the spread of the religion. Additionally, this article examines the contribution of artistic traditions such as the Gandhara, Mathura and Amaravati schools, which influenced Buddhist art and iconography. The rise of Buddhism marks a transformative period in India's spiritual and cultural history, which influenced future religious movements and left a lasting impact on both Indian and global philosophical thought. In addition, this article highlights the significance of the development of Buddhist architecture and the interrelationship between Buddhism and other contemporary religious traditions, such as Jainism and early Hinduism. An analysis of the archaeological evidence attempts to shed light on the tangible legacy of early Buddhism, which reflects its lasting influence on art, culture and religious practices.